Experimental investigation on evacuated tube solar collector using biofluid as heat transfer fluid - Afolabi, Lukmon Owolabi; Afolabi-Owolabi, Oluwafunke; M. Elfaghi, Abdulhafid; Hissein Didane, Djamal; Awadh, Mohammed Ghaleb; Akram, Al-Mahmodi (Penerbit Akademia Baru, 2021)
Bio-oil extracted from waste of different plant kernel was used as heat transfer fluid in evacuated tube solar collector. Thermal performance of the biofluids to the enhancement of the evacuated tube solar collector under varying weather conditions and experimental analysis was carried-out. Thermal analysis on the storage water tank temperature, outlet and inlet heat transfer fluid temperature, and heat gains by was studied. In addition, the biofluids thermophysical properties and degradation analysis was conducted and compared with conventional base-fluids. From the results the biofluids caused enhancement of heat gain in the collector receiver by 9.5%, 6.4% and 3.2% for moringa oleifera kernel oil (MOKO), date kernel oil (DKO) and palm kernel oil (PKO), respectively. The storage water tank temperature at night fall was 53, 49, 51 and 47oC, for the MOKO, DKO, PKO and water HTFs, respectively. The biofluids were thermal stable and with no degradation. The biofluids demonstrated potentials as heat transfer fluids in thermal applications but there are needs for more investigations on their enhancement with organically synthesized nano particles to preserve there no corrosive and toxicity nature, and experimental performance on heat exchangers after several heating cycles.